Factors associated with depressive symptoms in elderly caregivers with chronic pain - Marielli Terassi; Estefani Serafim Rossetti; Bruna Moretti Luchesi; Karina Gramani-Say; Priscilla Hortense; Sofia Cristina Iost Pavarini (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to identify factors associated with depressive symptoms in elderly caregivers with chronic pain. Method: the study included people 60 years of age or older who reported chronic pain and cared for another elderly person living in the same household (n=186). Statistical analyzes were performed using the Mann-Whitney test, univariate and multiple logistic regression. Results: most participants had no depressive symptoms (70.4%), 24.2% had mild depressive symptoms and 5.4% had severe symptoms. Univariate analysis showed that the variables family income, number of diseases, number of medications in use, pain intensity, overload and perceived stress were associated with depressive symptoms. Multivariate analysis found an association with perceived stress (95% CI 1.101-1207) and number of medications (95% CI 1.139-1.540) in use. Conclusion: factors associated with depressive symptoms in elderly caregivers with chronic pain were stress and the number of medications in use.